A lithium-ion battery silicon-carbon negative electrode material with an inner and outer multi-level core-shell structure and a preparation method thereof

Through the silicon-carbon anode material of lithium-ion battery with internal and external multi-stage core-shell structure, combined with KOH chemical activation and corn starch porous structure, the volume expansion and low conductivity of Si-based anode material are solved, and the activity and cyclic stability of the electrode material are significantly improved.

CN116207231BActive Publication Date: 2025-03-14KUNMING UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310212597.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-07
Publication Date
2025-03-14
Estimated Expiration
2043-03-07

AI Technical Summary

Technical Problem

The Si-based negative electrode material in lithium-ion batteries has rapidly attenuated electrode performance due to problems such as volume expansion, low conductivity and unstable solid-electrolyte interface film (SEI).

Method used

The silicon-carbon anode material of lithium-ion battery with multi-stage core-shell structures is prepared by KOH chemical activation method, and a porous structure is constructed using corn starch, combined with nanosilicon and porous carbon to form a carbon shell to alleviate volume expansion and improve conductivity.

Benefits of technology

It significantly improves the activity and cyclic stability of the electrode material, improves the transfer rate of lithium ion, reduces the first irreversible capacity, and improves the electrochemical reaction capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116207231B_ABST
    Figure CN116207231B_ABST
Patent Text Reader

Abstract

The present invention discloses a lithium-ion battery silicon-carbon negative electrode material with an inner and outer multi-level core-shell structure and a preparation method thereof, belonging to the technical field of lithium-ion battery negative electrode materials; the present invention chemically activates corn starch by KOH, constructs a porous structure in its particles, and obtains a biomass porous carbon skeleton; the obtained biomass porous carbon skeleton is composited with nano-silicon by heating in a water bath; and finally the silicon-carbon composite material is coated by resorcinol / formaldehyde to obtain a lithium-ion battery silicon-carbon negative electrode material with an inner and outer multi-level core-shell structure. The present invention overcomes the problem in the prior art that the solid electrolyte interface film (SEI) on the particle surface is destroyed and the capacity loss is serious due to the volume expansion of the silicon-based negative electrode material itself.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a lithium ion battery silicon-carbon negative electrode material with an inner and outer multi-level core-shell structure and a preparation method thereof, belonging to the technical field of lithium ion battery negative electrode materials. Background Art

[0002] In recent years, with the development of science and technology, the research and innovation of energy storage devices has become increasingly important. Although lithium-ion batteries are one of the most well-developed energy storage devices, the theoretical capacity of their commercial graphite anode is only 372 mAh g -1 , which can no longer meet the needs of the development of the lithium-ion battery market. Therefore, highly reversible lithium alloy materials (such as Si, Ge, Sn) have been used as negative electrode materials for lithium-ion batteries. Among them, Si-based materials, due to their ultra-high theoretical capacity (4200 mAh g -1 ), is considered to be an ideal substitute for graphite anode. However, Si-based anode materials will undergo huge volume expansion / contraction (300%) during the charge and discharge cycle, which leads to rapid attenuation of electrode performance. In addition, due to the poor conductivity of Si itself, its practical application is also seriously affected. In order to solve the problems of high volume expansion, low conductivity and unstable solid electrolyte interface (SEI) inherent in the silicon anode of lithium-ion batteries, the development of a new type of silicon-carbon anode material with high energy density, low cost and stable cycle has become a hot topic in battery material research in recent years.

[0003] In view of the problems faced by the above-mentioned Si-based negative electrode materials, the current research focuses mainly on: ① The volume of silicon negative electrode materials is constantly in a state of expansion and contraction during the charging and discharging process, and the large internal stress will cause the active particles to pulverize and break. The pulverized particles will continue to react with the electrolyte to form a new solid-electrolyte interface film, causing the film thickness to increase continuously and the loss of reversible capacity. ② As the cycle continues, the pulverized and broken particles will cause the electrode coating to fall off from the current collector, and they will not be able to contribute capacity after losing electrical contact. The large volume expansion of silicon particles and the lack of buffer space inside the electrode will cause the electrode to continue to expand and thicken toward the surface. ③ The continuous volume change of the silicon negative electrode will cause the SEI film on the electrode surface to become thicker and thicker, reducing the conductivity and utilization rate of the active material. The present invention provides a lithium-ion battery silicon-carbon negative electrode material with an internal and external multi-level core-shell structure and a preparation method thereof, which effectively constructs a carbon skeleton to alleviate the volume expansion problem of nano-silicon materials, improve the activity of electrode materials, and make the comprehensive electrochemical performance more stable. Summary of the invention

[0004] Aiming at the problems of low conductivity, slow lithium ion migration rate, high first irreversible capacity, poor cycle performance and the like caused by the volume effect of silicon negative electrode materials; the present invention provides a lithium ion battery silicon-carbon negative electrode material with an internal and external multi-level core-shell structure and a preparation method thereof. The present invention prepares the lithium ion battery silicon-carbon negative electrode material with an internal and external multi-level core-shell structure by a simple KOH chemical activation method, constructs a porous structure in corn starch particles, obtains a biomass porous carbon-carbon skeleton composited with nano-silicon and coated with a carbon shell; on the one hand, the porous carbon structure provides more and more stable diffusion channels for the migration of lithium ions between material particles, and on the other hand, the introduction of nano-silicon can significantly improve the conductivity of the electrode material, and alleviate the volume expansion problem of the nano-silicon material, thereby improving the electrochemical reaction capacity.

[0005] The invention is realized by a simple chemical activation KOH etching method, wherein corn starch is used as a raw material, gelatinized starch is synthesized under certain conditions; then, starch-based activated carbon is obtained through high-temperature sintering; the starch-based activated carbon is washed, filtered and dried with hydrochloric acid and deionized water to obtain corn starch porous carbon; the corn starch porous carbon and a nano-silicon material composite material are heated and compounded in a water bath to obtain a silicon-carbon material composite material precursor, and then resorcinol and formaldehyde are added to coat the silicon-carbon material composite material precursor, and then the precursor is moved into a vacuum tube furnace to further optimize the precursor morphology structure; finally, the lithium ion battery silicon-carbon negative electrode material with an inner and outer multi-level core-shell structure is obtained through grinding and sieving.

[0006] The preparation method of the lithium ion battery silicon-carbon negative electrode material of the inner and outer multi-level core-shell structure of the present invention is as follows:

[0007] (1) Add corn starch and KOH to a mixed solvent of ethanol and deionized water in a certain mass ratio, mix the solution, and stir it with a magnetic stirrer for 25 to 30 minutes at room temperature to form a uniform starch dispersion;

[0008] (2) placing the starch dispersion of step (1) in an oven at 60° C. to 100° C. for 6 to 12 hours until the solvent is completely evaporated to obtain gelatinized starch;

[0009] (3) placing the gelatinized starch obtained in step (2) into a vacuum tube furnace, heating the mixture from room temperature to 600°C to 750°C at a rate of 3 to 10°C / min under the protection of a nitrogen or argon atmosphere, and maintaining the temperature for 1.8 to 2.2 hours to anneal and convert the starch into starch-based activated carbon;

[0010] (4) washing the starch-based activated carbon prepared in step (3) with hydrochloric acid to remove unreacted KOH and potassium-containing compounds, then washing and filtering with deionized water for 3 to 5 times until the pH value of the filtrate is 7; finally drying in a drying oven at 60 to 100° C. for 3 to 8 hours to obtain a corn starch porous carbon material;

[0011] (5) adding a certain amount of Si nanoparticles to a mixed solvent of ethanol and deionized water and ultrasonicating for 0.5 to 3 hours, then adding the corn starch porous carbon material of step (4) to compound with the nano-silicon under heating conditions in a water bath, adding a certain amount of resorcinol and formaldehyde at room temperature and stirring for 0.5 to 3 hours, and then drying at 60 to 100° C. under vacuum to obtain a silicon-carbon composite material precursor;

[0012] (6) The silicon-carbon composite material precursor obtained in step (5) is placed in a vacuum tube furnace, and under the protection of a nitrogen or argon atmosphere, the temperature is raised to 700°C~850°C at a rate of 5~15°C / min and kept at this temperature for 2 hours. After cooling to room temperature, the precursor is taken out, ground, and sieved to obtain a lithium-ion battery silicon-carbon negative electrode material with an inner and outer multi-level core-shell structure.

[0013] In step (1), the mass ratio of corn starch to KOH is 1:1 to 1:3.

[0014] In step (5), the mass ratio of corn starch porous carbon material, resorcinol and formaldehyde is 2:1:1~2:1.5:1.5.

[0015] In step (5), the mass ratio of nano silicon particles to corn starch porous carbon material is 3:7 to 4:6.

[0016] The mixed solution of ethanol and deionized water in steps (1) and (5) is prepared by mixing ethanol and deionized water in a volume ratio of 1:1 to 1:2. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is a scanning electron microscope image of corn porous carbon prepared in Example 1 of the present invention;

[0018] Figure 2 This is a scanning electron microscope image of a lithium-ion battery silicon-carbon negative electrode material with an inner and outer multi-level core-shell structure prepared in Example 2 of the present invention;

[0019] Figure 3 This is a charge and discharge curve diagram of the lithium-ion battery silicon-carbon negative electrode material with an inner and outer multi-level core-shell structure prepared in Example 3 of the present invention;

[0020] Figure 4 This is the electrochemical cycle diagram of the lithium-ion battery silicon-carbon negative electrode material with an inner and outer multi-level core-shell structure according to Preparation Example 3 of the present invention. Implementation

[0021] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, but the protection scope of the present invention is not limited to the described contents. Example 1

[0022] The preparation method of the lithium ion battery silicon-carbon negative electrode material of the inner and outer multi-level core-shell structure of the present invention is as follows:

[0023] (1) Corn starch and KOH were added to a mixed solvent of ethanol and deionized water (volume ratio 1:1) in a certain mass ratio, and the solution was mixed and stirred with a magnetic stirrer for 25 minutes at room temperature to form a uniform starch dispersion;

[0024] (2) placing the starch dispersion of step (1) in an oven at 80° C. for 8 hours until the solvent is completely evaporated to obtain gelatinized starch;

[0025] (3) placing the gelatinized starch obtained in step (2) into a vacuum tube furnace, heating the temperature from room temperature to 700° C. at a rate of 3° C. / min under the protection of a nitrogen or argon atmosphere and keeping the temperature for 2 hours to anneal and convert it into starch-based activated carbon;

[0026] (4) washing the starch-based activated carbon prepared in step (3) with hydrochloric acid to remove unreacted KOH and potassium-containing compounds, then washing and filtering with deionized water for three times until the pH of the filtrate is 7; finally drying in a drying oven at 60° C. for 8 hours to obtain a corn starch porous carbon material;

[0027] (5) A certain amount of Si nanoparticles (particle size of 30-500 nm) was added to a mixed solvent of ethanol and deionized water and ultrasonicated for 0.5 hours. The corn starch porous carbon material of step (4) was then added to the nano-silicon under heating conditions in a water bath, and a certain amount of resorcinol and formaldehyde were added at room temperature and stirred for 2 hours (the mass ratio of corn starch porous carbon material, resorcinol and formaldehyde was 2:1:1), and then dried at 60°C under vacuum to obtain a silicon-carbon composite material precursor;

[0028] (6) The silicon-carbon composite material precursor obtained in step (5) is placed in a vacuum tube furnace, and under the protection of a nitrogen or argon atmosphere, the temperature is raised to 750°C at a rate of 5°C / min and kept at this temperature for 2 hours. After cooling to room temperature, the precursor is taken out, ground, and sieved to obtain a lithium-ion battery silicon-carbon negative electrode material with an inner and outer multi-level core-shell structure.

[0029] The scanning electron microscope image of the corn porous carbon material prepared in this example is as follows: Figure 1 As shown, it can be clearly observed that the corn starch carbon has evenly distributed micropores and an uneven surface with protrusions and depressions. Example 2

[0030] The preparation method of the lithium ion battery silicon-carbon negative electrode material of the inner and outer multi-level core-shell structure of the present invention is as follows:

[0031] (1) Add corn starch and KOH to a mixed solvent of ethanol and deionized water (volume ratio 1:2) in a certain mass ratio, mix the solution, and stir it with a magnetic stirrer for 25 to 30 minutes at room temperature to form a uniform starch dispersion;

[0032] (2) placing the starch dispersion of step (1) in an oven at 60° C. for 12 hours until the solvent is completely evaporated to obtain gelatinized starch;

[0033] (3) placing the gelatinized starch obtained in step (2) into a vacuum tube furnace, heating the temperature from room temperature to 750° C. at a rate of 5° C. / min under the protection of a nitrogen or argon atmosphere and keeping the temperature for 2 hours to anneal and convert it into starch-based activated carbon;

[0034] (4) washing the starch-based activated carbon prepared in step (3) with hydrochloric acid to remove unreacted KOH and potassium-containing compounds, then washing and filtering with deionized water for 3 times until the pH value of the filtrate is 7; finally drying in a drying oven at 100° C. for 6 hours to obtain a corn starch porous carbon material;

[0035] (5) A certain amount of Si nanoparticles (particle size of 30-500 nm) was added to a mixed solvent of ethanol and deionized water and ultrasonicated for 1 hour. Then, the corn starch porous carbon material of step (4) was added and composited with nano-silicon under heating conditions in a water bath. A certain amount of resorcinol and formaldehyde were added at room temperature and stirred for 3 hours (the mass ratio of corn starch porous carbon material, resorcinol and formaldehyde was 2:1:1). Then, the mixture was dried at 80°C under vacuum to obtain a silicon-carbon composite material precursor.

[0036] (6) The silicon-carbon composite material precursor obtained in step (5) is placed in a vacuum tube furnace, and under the protection of a nitrogen or argon atmosphere, the temperature is raised to 850°C at a rate of 5°C / min and kept at this temperature for 2 hours. After cooling to room temperature, the precursor is taken out, ground, and sieved to obtain a lithium-ion battery silicon-carbon negative electrode material with an inner and outer multi-level core-shell structure.

[0037] The scanning electron microscope of the lithium ion battery silicon-carbon negative electrode material with a multi-level core-shell structure prepared in this embodiment is as follows: Figure 2 As shown, it can be seen that nano-silicon and corn starch porous carbon are composited together and coated with a carbon shell to inhibit the volume expansion of the nano-silicon material, giving the material better cycle stability. Example 3

[0038] The preparation method of the lithium ion battery silicon-carbon negative electrode material of the inner and outer multi-level core-shell structure of the present invention is as follows:

[0039] (1) Add corn starch and KOH to a mixed solvent of ethanol and deionized water (volume ratio 1:1) in a certain mass ratio, mix the solution, and stir it with a magnetic stirrer for 25 to 30 minutes at room temperature to form a uniform starch dispersion;

[0040] (2) placing the starch dispersion of step (1) in an oven at 100° C. for 6 hours until the solvent is completely evaporated to obtain gelatinized starch;

[0041] (3) placing the gelatinized starch obtained in step (2) into a vacuum tube furnace, heating the mixture from room temperature to 650° C. at a rate of 4° C. / min under the protection of a nitrogen or argon atmosphere and maintaining the temperature for 2 hours to anneal and convert the mixture into starch-based activated carbon;

[0042] (4) washing the starch-based activated carbon prepared in step (3) with hydrochloric acid to remove unreacted KOH and potassium-containing compounds, then washing and filtering with deionized water for three times until the pH of the filtrate reaches 7; finally drying in a drying oven at 100° C. for 5 hours to obtain a corn starch porous carbon material;

[0043] (5) A certain amount of Si nanoparticles (particle size of 30-500 nm) was added to a mixed solvent of ethanol and deionized water and ultrasonicated for 2 hours. The corn starch porous carbon material of step (4) was then added to composite with nano-silicon under heating conditions in a water bath. A certain amount of resorcinol and formaldehyde were added at room temperature and stirred for 2.5 hours (the mass ratio of corn starch porous carbon material, resorcinol and formaldehyde was 2:1:1). The mixture was then dried at 100°C under vacuum to obtain a silicon-carbon composite material precursor.

[0044] (6) The silicon-carbon composite material precursor obtained in step (5) is placed in a vacuum tube furnace, and under the protection of a nitrogen or argon atmosphere, the temperature is raised to 800°C at a rate of 8°C / min and kept at this temperature for 2 hours. After cooling to room temperature, the precursor is taken out, ground, and sieved to obtain a lithium-ion battery silicon-carbon negative electrode material with an inner and outer multi-level core-shell structure.

[0045] Weigh 0.12 g of the composite material prepared in this embodiment, 0.04 g of acetylene black, and 0.04 g of sodium alginate, first add 1 ml of deionized water, then put the above three chemicals into a mortar in turn, grind for 30 minutes, evenly apply the viscous mixture on the copper foil, then preliminarily dry it at 80°C for 15 minutes, and then dry it in a vacuum oven at 80°C for 12 hours, then roll the copper foil, and then cut it into discs with a diameter of 14 mm to obtain an electrode.

[0046] In a glove box filled with argon (O2 content <1 ppm, water content <1 ppm), the electrode, diaphragm, lithium sheet and nickel foam mesh were assembled into a button cell by conventional methods. -1The battery electrochemical performance test was carried out on a constant current charge and discharge system at a rate of Figure 3 As shown in the figure, it can be seen that the scanning rate is 0.2 mVs −1 Under the condition of , constant current discharge-charge test was carried out between 0.01 and 2.0V to examine the electrochemical reactivity of the sample. Compared with the tenth cycle of charge and discharge, there was a greater energy loss in the first cycle, but the energy loss in the fiftieth and one hundredth cycles was relatively small, and the material was relatively stable; the cycle results are shown in the figure Figure 4 As shown in the figure, the battery chemical stability of pure nano-silicon material is poor and has been declining. Although the prepared corn porous carbon material has a low capacity, it is relatively stable. The prepared porous carbon embedded nano-silicon composite coated carbon shell lithium ion battery composite negative electrode material has strong stability and the battery capacity is maintained at 875 mAh g -1 . Example 4

[0047] The preparation method of the porous carbon embedded nano-silicon composite coated carbon shell lithium ion battery composite negative electrode material is as follows:

[0048] (1) Add corn starch and KOH to a mixed solvent of ethanol and deionized water (volume ratio 1:1) in a certain mass ratio, mix the solution, and stir it with a magnetic stirrer for 25 to 30 minutes at room temperature to form a uniform starch dispersion;

[0049] (2) placing the starch dispersion of step (1) in an oven at 100° C. for 6 hours until the solvent is completely evaporated to obtain gelatinized starch;

[0050] (3) placing the gelatinized starch obtained in step (2) into a vacuum tube furnace, heating the mixture from room temperature to 650° C. at a rate of 4° C. / min under the protection of a nitrogen or argon atmosphere and maintaining the temperature for 2 hours to anneal and convert the mixture into starch-based activated carbon;

[0051] (4) washing the starch-based activated carbon prepared in step (3) with hydrochloric acid to remove unreacted KOH and potassium-containing compounds, then washing and filtering with deionized water for three times until the pH of the filtrate reaches 7; finally drying in a drying oven at 100° C. for 5 hours to obtain a corn starch porous carbon material;

[0052] (5) A certain amount of Si nanoparticles (particle size of 30-500 nm) was added to a mixed solvent of ethanol and deionized water and ultrasonicated for 2 hours. The corn starch porous carbon material of step (4) was then added to composite with nano-silicon under heating conditions in a water bath. A certain amount of resorcinol and formaldehyde were added at room temperature and stirred for 2.5 hours (the mass ratio of corn starch porous carbon material, resorcinol and formaldehyde was 2:1.5:1.5), and then dried at 100°C under vacuum to obtain a silicon-carbon composite material precursor.

[0053] (6) The silicon-carbon composite material precursor obtained in step (5) is placed in a vacuum tube furnace, and under the protection of a nitrogen or argon atmosphere, the temperature is raised to 800°C at a rate of 8°C / min and kept at this temperature for 2 hours. After cooling to room temperature, the precursor is taken out, ground, and sieved to obtain a lithium-ion battery silicon-carbon negative electrode material with an inner and outer multi-level core-shell structure.

[0054] The present invention prepares a lithium-ion battery silicon-carbon negative electrode material with an internal and external multi-level core-shell structure by a simple KOH chemical activation method, constructs a porous structure in corn starch, obtains a biomass porous carbon-carbon skeleton composited with nano-silicon and coated with a carbon shell, and utilizes the porous carbon structure to provide more and more stable diffusion channels for the migration of lithium ions between material particles; with the help of nano-silicon, the volume expansion problem of nano-silicon materials is alleviated to improve the electrochemical reaction capacity. In addition, during the cycle of the coated carbon layer shell, there are a large number of gaps between the Si core and the outer carbon shell to adapt to the volume expansion of Si and form a stable SEI layer; the presence of the carbon layer avoids direct contact between Si nanoparticles and electrolytes, and promotes the formation of a stable SEI and the lithiation process, thereby significantly improving the cycle stability of the composite material. The above is a detailed description of the specific embodiments of the present invention in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by ordinary technicians in this field, various changes can be made without departing from the purpose of the present invention.

Claims

1. A method for preparing a lithium-ion battery silicon-carbon negative electrode material with an internal and external multi-level core-shell structure, characterized in that: The specific steps are as follows: (1) Add corn starch and KOH to a mixed solvent of ethanol and deionized water in a certain mass ratio, mix the solution, and stir it with a magnetic stirrer for 25 to 30 minutes at room temperature to form a uniform starch dispersion; (2) placing the starch dispersion of step (1) in an oven at 60° C. to 100° C. for 6 to 12 hours until the solvent is completely evaporated to obtain gelatinized starch; (3) placing the gelatinized starch obtained in step (2) into a vacuum tube furnace, heating the mixture from room temperature to 600°C to 750°C at a rate of 3 to 10°C / min under the protection of a nitrogen or argon atmosphere, and maintaining the temperature for 1.8 to 2.2 hours to anneal and convert the starch into starch-based activated carbon; (4) washing the starch-based activated carbon prepared in step (3) with hydrochloric acid to remove unreacted KOH and potassium-containing compounds, then washing and filtering with deionized water for 3 to 5 times until the pH value of the filtrate is 7; finally drying in a drying oven at 60 to 100° C. for 3 to 8 hours to obtain a corn starch porous carbon material; (5) adding a certain amount of Si nanoparticles to a mixed solvent of ethanol and deionized water and ultrasonicating for 0.5 to 3 hours, then compounding the corn starch porous carbon material of step (4) with nano-silicon under heating conditions in a water bath, adding a certain amount of resorcinol and formaldehyde at room temperature and stirring for 0.5 to 3 hours, and then drying at 60 to 100° C. under vacuum to obtain a silicon-carbon composite material precursor; (6) The silicon-carbon composite material precursor obtained in step (5) is placed in a vacuum tube furnace, and under the protection of a nitrogen or argon atmosphere, the temperature is raised to 700°C~850°C at a rate of 5~15°C / min and kept at this temperature for 2 hours. After cooling to room temperature, the precursor is taken out, ground, and sieved to obtain a lithium-ion battery silicon-carbon negative electrode material with an inner and outer multi-level core-shell structure.

2. The method for preparing the lithium-ion battery silicon-carbon negative electrode material with an internal and external multi-level core-shell structure according to claim 1, characterized in that: The mass ratio of corn starch to KOH in step (1) is 1:1 to 1:

3.

3. The method for preparing the lithium ion battery silicon-carbon negative electrode material with an internal and external multi-level core-shell structure according to claim 1, characterized in that: In step (5), the mass ratio of nano silicon particles to corn starch porous carbon material is 3:7 to 4:

6.

4. The method for preparing the lithium-ion battery silicon-carbon negative electrode material with an internal and external multi-level core-shell structure according to claim 1, characterized in that: In step (5), the mass ratio of corn starch porous carbon material, resorcinol and formaldehyde is 2:1:1~2:1.5:1.

5.

5. The method for preparing the lithium-ion battery silicon-carbon negative electrode material with an internal and external multi-level core-shell structure according to claim 1, characterized in that: The mixed solution of ethanol and deionized water in step (1) and step (5) is prepared by mixing ethanol and deionized water in a volume ratio of 1:1 to 1:

2.

6. The method for preparing the lithium-ion battery silicon-carbon negative electrode material with an internal and external multi-level core-shell structure according to claim 1, characterized in that: The size of the Si nanoparticles in step (5) is 30-500 nm.

7. A lithium-ion battery silicon-carbon negative electrode material with an inner and outer multi-level core-shell structure prepared by the preparation method according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Preparation method of lithium ion battery carbon-silicon negative electrode material

    CN111153394A

  • Controllable synthesis method of yolk-shell type silicon / carbon composite negative electrode material

    CN112436130A